STRATEGI ARGENTINA MEMPERLUAS WILAYAH KEDAULATAN TAHUN 2009 – 2016 - Muhammad Wawan Ramadhan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This paper aims to explain Argentina‟s goal in increasing its maritime territory through the UN. Argentina submitted the expansion of the continental shelf area through UN-CLCS (united Nation Commission on the limits of the Continental Shelf). The UN Approved the reccommendations issued by UN-CLCS which changed Argentina‟s marritime territory to more than 35%.This research is using qualitative method with library research. The data were obtained from books, journals, mass media websites, and relevant document in research. This research relies on structural realism or neorealism perspective by Kenneth Waltz with foreign policy theory from James N. Rossenau. Level of analysis used in this research is nation-state.Argentina Submitted the extent of hte continental Shelf to UN-CLCS in 2009. After a long process, the UN finally approved the recommendations provided by CLCS as the body of the UNCLOS paragraph 76 and 77on March 11, 2016. Argentina‟s marritime territory increased and changed Argentine geopolitical map. The Malvinas Island lies in Argentina territory. It is become easier for Argentina to win the Malvinas dispute with Britain which has been going on for a long time.Keywords : UN-CLCS, UNCLOS, Continental Shelf, Foreign Policy